Unveiling the Interplay of Triple Bottom Line and Blue Economy in Empowering Coastal MSMEs of East Java towards Sustainable Export Capacity (SDGs) - Pratama, Devangga Putra Adhitya; Farida, Nur (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
This study investigates the persistent challenges faced by coastal Micro, Small, and Medium Enterprises (MSMEs) in East Java, whose export capacity remains limited despite their substantial economic contribution. A conceptual model integrating the Triple Bottom Line (economic, social, and environmental dimensions) with the Blue Economy framework as a mediating variable was developed and tested. The research employed a quantitative design using survey data from 250 coastal MSMEs and analyzed through Structural Equation Modeling (SEM). The results reveal that the environmental dimension exerts the strongest and most significant influence on sustainable export capacity (β = 0.47, p < 0.01), while the economic (β = 0.29, p < 0.05) and social (β = 0.21, p < 0.05) dimensions become more effective when mediated by Blue Economy principles. These findings highlight that coastal MSME empowerment requires multidimensional strategies that balance profit, people, and planet while leveraging blue economy innovation. The novelty of this study lies in extending TBL applications beyond corporate settings toward export-oriented MSMEs, contributing to sustainability literature and offering practical implications for advancing the Asta Cita 2 and Sustainable Development Goals (SDG 8, 12, 14).